2018
DOI: 10.1073/pnas.1804177115
|View full text |Cite
|
Sign up to set email alerts
|

Relation between single-molecule properties and phase behavior of intrinsically disordered proteins

Abstract: Proteins that undergo liquid-liquid phase separation (LLPS) have been shown to play a critical role in many physiological functions through formation of condensed liquid-like assemblies that function as membraneless organelles within biological systems. To understand how different proteins may contribute differently to these assemblies and their functions, it is important to understand the molecular driving forces of phase separation and characterize their phase boundaries and material properties. Experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
463
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 324 publications
(537 citation statements)
references
References 74 publications
29
463
3
Order By: Relevance
“…[129][130][131] In this context, progress has nonetheless been made in theoreticalp hysical understanding of how LLPS of IPDs might depend on their amino acid sequences by using coarse-grained approaches. These include analytical theory, [33,38,61,132,133] lattice [134] and continuum [9,135,136] residuebased explicit-chain models, [137] and field theory simulations. [138,139] These studies indicate that LLPS is sensitiven ot only to the net electric charge of an IDP buta lso the pattern of charged istribution along its sequence.…”
Section: At Entative Rationalization Of T- P- and Tmao-dependentpromentioning
confidence: 99%
“…[129][130][131] In this context, progress has nonetheless been made in theoreticalp hysical understanding of how LLPS of IPDs might depend on their amino acid sequences by using coarse-grained approaches. These include analytical theory, [33,38,61,132,133] lattice [134] and continuum [9,135,136] residuebased explicit-chain models, [137] and field theory simulations. [138,139] These studies indicate that LLPS is sensitiven ot only to the net electric charge of an IDP buta lso the pattern of charged istribution along its sequence.…”
Section: At Entative Rationalization Of T- P- and Tmao-dependentpromentioning
confidence: 99%
“…To further elucidate the potential contributions of hydrophobicity vs. helicity to TDP-43 phase separation, we conducted coarse-grained simulations of TDP-43 CTD coexistence following the simulation model and framework from our previous work [46][47][48] . Because this coarse-grained model treats protein chains as flexible polymers and secondary structure is not directly captured, this allows us to decouple the mutational change in hydrophobicity from the changes in helicity, which are inseparable in experiment and traditional all-atom molecular simulation.…”
Section: G335 and G338 Mutations Enhance Intermolecular Helix-helix Cmentioning
confidence: 99%
“…20,28,[34][35][36] We also found that the θ-temperature (T θ ) of a single chain, the temperature at which ν=0.5, is strongly correlated with the critical temperature (T c ) of liquid-liquid phase separation (LLPS) of disordered proteins. 37,38 This relationship provides a rapid method for approximating the behavior of IDPs in the context of LLPS, and aided in the development of a novel temperature-dependent interaction potential that explained upper-and lower critical solution temperature phase transitions based on temperature-dependent solvent-mediated interactions. 39 Given the role of polymer scaling properties in dictating the conformational behavior of IDPs, there have been significant efforts to predict ν as a function of the protein sequence or order parameters representing important sequence characteristics.…”
mentioning
confidence: 99%
“…The advantage of using ν as opposed to R g to characterize a protein's size is to eliminate the chain length dependence and to provide meaningful information on the solvent quality that can be useful in predicting protein LLPS. 37 We have recently shown that R g of a single protein can be used to estimate the scaling exponent (ν Rg ): 33,50,51…”
mentioning
confidence: 99%
See 1 more Smart Citation